An overview: Implementation and core elements of antimicrobial stewardship programme - Priyanshi Shah; Twinkle Maheshwari; Deepali Patel; Zinal Patel; Manoj S. Dikkatwar; Mrudangsinh M. Rathod (Elsevier, 2024)
Antimicrobial Stewardship Programme (ASP) is an organizational or system-wide health-care strategy that promotes optimal antibiotic use through the implementation of evidence-based interventions. The Indian Council of Medical Research (ICMR) issued the ASP guidelines in 2018, that are applicable for reducing antimicrobial resistance (AMR) effects. In comparison with older children, neonates receive broad spectrum antimicrobials more frequently. As neonates are having high risk of morbidity and mortality, so they are more susceptible to early upgradation of antibiotic. Antimicrobial use in terms of daily dose, cost, and treatment days, antimicrobial adverse events, resistance tendencies, intervention, and monitoring can all be utilized to assess an ASP's progress. An effective antimicrobial stewardship programme requires the presence of at least one infectious diseases-trained physician who devotes a portion of their time to the program's design, implementation, and operation. A pharmacist's most critical duties and responsibilities include developing, reviewing, and implementing antimicrobial stewardship (AMS) guidelines and policies, providing clinical guidance to optimise antimicrobial prescribing and usage, monitoring, auditing, and providing feedback. Clinical microbiology services are an essential component of successful AMS systems. Challenges in implementing Stewardship program are competition among doctors, absence of champion, utility value of an antibiogram, poor enforcement of regulations, time constraints, lack of inter-departmental co-ordination, minimal supporting facilities. A combination of particular antibodies, organism-specific bacteriophages, and small molecules might be used in future therapies that inhibit specific virulence factors, and antibiotic resistance-fighting drugs.